The Impact of Land Use on Hydrological Characteristics in Kaligarang Watershed - Susilo Budiyanto; S.D. Tarigan; N. Sinukaban; K. Murtilaksono (International Journal of Science and Engineering, 2015)
The increasing number of population in Kaligarang watershed will cause population pressure that will have a direct impact on land-use change and in turn will have an impact on watershed hydrological characteristics. Watershed management planning as an integral part of land-use and conservation based development is very important and need to be applied. The aims of this research were to analyze land-use changes in Kaligarang watershed, and the impact of land-use changes on watershed hydrological characteristics in Kaligarang. The results of this research showed that in Kaligarang watershed, there was a decrease in forest area of 2.28% and rice field of 13.96%, an increase in resident area of 2.14%, dry land farming of 5.82% and mixed dry land farming of 10.03%. The decreasing forest area caused an increase in runoff coefficien (CRO= 147.5 – 7.06F), an increase in average daily maximum discharge (Qmax(cms) = 79.33 – 4.23 F) and a decrease in baseflow (BF (cms) = -1.65 + 0.36 F)